Panlongqi tablet suppresses adjuvant-induced rheumatoid arthritis by inhibiting the inflammatory reponse in vivo and in vitro. (23rd May 2023) - Niu, Xiaofeng; Yang, Yajie; Yu, Jinjin; Song, Huixin; Yu, Jiabao; Huang, Qiuxia; Liu, Yang; Zhang, Dezhu; Han, Tengfei; Li, Weifeng
Abstract: Ethnopharmacological relevance: Panlongqi Tablet is prepared with the ancestral secret recipe provided by Mr. Wang Jiacheng, a famous specialist in orthopedics and traumatology of China. The efficacy and safety of PLQT have been supported by years of clinical practice in the treatment of joint-related conditions. Has remarkable effect for treating rheumatoid arthritis (RA) clinically. However, its mechanism is not entirely clear. Aim of the study: We aim to evaluate the anti-inflammatory activity of PLQT and explore its mechanism in adjuvant-induced arthritis (AA) mice and LPS-induced Human fibroblast-like synovial (HFLS) cells. Materials and methods: To this end, we analyzed the active ingredients in PLQT by HPLC-MS/MS. Furthermore, the anti-RA effect of PLQT was studied through proliferation, apoptosis, foot swelling, cytokine levels, immune organ index, histopathology and related signal pathways in LPS-induced HFLS cells and AA-treated mice. Results: HPLC-MS/MS results showed that PLQT contained a variety of active compounds, such as epicatechin, imperatorin, hydroxysafflor yellow A and so on. PLQT significantly inhibited the abnormal proliferation of HFLS cells induced by LPS, promoted cell apoptosis. In AA-treated mice, PLQT alleviated RA symptoms by alleviating paw swelling, synovial hyperplasia, pannus formation, inflammatory cell infiltration, and inhibiting abnormal immune responses. The results showed that PLQT significantly decreased the expression of inflammatory mediators (IL-1β, IL-6, IL-17) in vivo and in vitro, which may be related to the regulation of PI3K/Akt, MAPK and JAK/STAT signaling pathways. Conclusion: Based on serum pharmacology and in vivo pharmacology studies, PLQT may regulate RA symptoms by regulating inflammatory and immune response-related pathways, which is an effective method for the treatment of RA. Graphical abstract: Image 1 Highlights: PLQT contains a variety of active components, which have a good regulatory effect. PLQT inhibited the abnormal proliferation and promoted apoptosis. PLQT inhibited adjuvant-induced synovitis and pannus formation in mice. PLQT reduced the expression of inflammatory mediators in vivo and in vitro.